Blood Type and Outcomes in Pregnant Women with Placenta Previa. (25th January 2023) - Fan, Dazhi; Rao, Jiaming; Zhang, Huishan; Lin, Dongxin; Guo, Xiaoling; Liu, Zhengping
Abstract : Background . Placenta previa increases the risks of obstetrical complications. Many studies have reported a link between various ABO blood types and pregnancy complications. This study is aimed at describing and comparing the characteristics and outcomes of women with placenta previa by ABO blood type. Methods . Data for this study was obtained from a retrospective cohort study between January 1, 2014, and June 30, 2019, of all clinically confirmed placenta previa in a university-based tertiary medical center. Both types of A, B, O, AB, and combining O and non-O blood types were compared to the characteristics and outcomes. Results . 1678 participants with placenta previa were included in this study. The highest participants were blood type O with 666 (39.7%), followed by type A with 508 (30.3%) and type B with 395 (23.5%), and the lowest participants were AB with 109 (6.5%). Blood type AB had a higher incidence of antepartum hemorrhage (p = 0.017 ), predelivery anemia (p = 0.036 ), and preterm birth (p = 0.015 ) in placenta previa women. Meanwhile, the incidence of rhesus D positive (97.9% vs. 95.8%, p = 0.012 ) and twins (5.0% vs. 2.7%, p = 0.011 ) was higher in the non-O group, and the incidence of neonatal asphyxia (5.9% vs. 9.2%, p = 0.016 ) was lower in the non-O group. Conclusion . Type AB blood may be a potential risk factor for women with placenta previa. This finding may help provide any obstetrician to predict the risk of complication for placenta previa women by the ABO blood types.